PEMANFAATAN MEDIA PEMBELAJARAN WAYANG CERITA UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK PESERTA DIDIK DI SEKOLAH DASAR - Adam Bahari; Ipan Maulana; Balkis Bilbina; Patra Aghtiar Rakhman (Jurnal Genta Mulia, 2025)
This study aims to determine the effect of the use of puppet media on the improvement of listening skills in students at SDN Karundang 1 Serang City. Using a qualitative approach with a descriptive method, this study collects data through interviews, observations, and documentation. The results of the study show that the use of story puppet media can significantly improve students' listening skills. This media has succeeded in attracting students' attention and motivation, as well as making learning more fun and interactive. Students showed improvement in story comprehension, participation in discussions, and mastery of new vocabulary. In addition, puppet media also plays a role in introducing local cultural values. Although there are several challenges, such as the limited number of physical puppets, the use of digital media can be an effective solution. Overall, the use of wayang cerita media has proven to make a great contribution to the improvement of listening skills and the development of students' communication skills in elementary school.